Efecto de inoculación con rizobacterias en el crecimiento y producción de tres variedades de soya (Glicyne max L) en el cantón Quevedo - Cedeño Saavedra, Damián Antonio (2016)
Soy production has been affected by climate variability, which has become visible in the fluctuation of production levels, so it was necessary to investigate in wet conditions remaining in the area of Quevedo in the Laboratory of Microbiology environmental and Plant Biotechnology Department of the State Technical University of Quevedo, in order to determine the effect of inoculation with rhizobacteria on growth and production of three varieties of soybean (Glicyne max L), quantifying the morphological character length and number roots in three soybean varieties, treated with Bradyrhizobium japonicum and Pseudomonas spp in vitro, verifying the formation of nodules in three soybean varieties to be inoculated Bradyrhizobium japonicum and Pseudomonas spp, in greenhouses, and analyzing the morphological response rizobacterias for physiological stage of production. The treatments tested were constituted by two factors: three varieties and four strains (rizobacterias) with which twelve treatments were subjected to analysis of variance and Tukey test at 0.05 level were established. Characters, radicle length and number of rootlets, plant height, main root length, the total number of nodules, days to flowering, number of pods, and weight of 100 seeds performance were evaluated. Analysis and interpretation of the results it is concluded: The bacterium Bradyrhizobium japonicum had a positive effect on root growth at 7 days germinating in- vitro in soybean variety ICA-P34 and Iniap 307, but not in Iniap 308, the CHA0 bacterial inoculants Pseudomonas fluorescens and Pseudomonas veronii R4 showed a significant effect for the study of this variable highest number of rootlets was observed in 307 Iniap variety when treated with Bradyrhizobium japonicum. In nodulation bacteria Bradyrhizobium japonicum present as many numbers of nodules in the variety Iniap 308 seeing its effectiveness in the interaction genotype - strain, and no nodule formation when exposed to solution containing Pseudomonas fluorescens CHA0 and Pseudomonas veronii R4. When applied rizobacteria Bradyrhizobium japonicum slightly sped up the number of days to flowering compared with each variety without rizobacteria. The highest number of pods was obtained when applied Bradyrhizobium japonicum confirming the positive of Bradyrhizobium japonicum in the ICA-P34 and Iniap-307 varieties in what you have to do the weight of 100 seeds. x